Behavioral intention to use M-learning among higher education undergraduates / Adam Afandi - Afandi, Adam (Faculty of Business Management, 2017)
M-learning is no longer isolated in Malaysian education sector. It enables students to use their mobile devices for self-learning anywhere and anytime. This study hopes to provide further understanding of students’ acceptance towards m-learning and all the benefits that is yet to be discovered. A descriptive study is being conducted for this research whereby data is being collected from 93 respondents. Five point Likert scale questionnaires are being distributed to the respondents among students of UiTM Malacca City Campus and simple random sampling method was used in this research. The data obtained is being analyzed using Reliability Test, Pearson Correlation Coefficient Statistic, and Multiple Regression Analysis was conducted in this research. The objectives of this study are to identify determinants factors that drive the behavioral intention to use m-learning.The result from the study indicate that all of the independent variables (performance expectancy, effort expectancy, lecturers’ influence, quality of service, and personal innovativeness) had a significant relationship towards behavioral intention to use m-learning while the most influential determinants towards behavioral intention to use m-learning is effort expectancy.